Pidge, Texas Ranger - Parsons, Chuck (Book collections on Project MUSE., 2013)
Thomas C. (Pidge) Robinson came to Texas from Virginia at the age of 27, fleeing a feud with a neighbor who opposed Robinson?s amorous intentions toward the neighbor?s sister. He joined the Texas Rangers in 1874, serving with legendary Capt. Leander H. McNelly?s Washington County Volunteer Militia Company A. He earned the rank of first lieutenant in this Texas Ranger company. Two years later he returned to Virginia to avenge his honor and claim the woman he loved. A learned and witty writer who sent back letters, poems, and reports for publication in Austin newspapers, Pidge also wrote most of Captain McNelly?s reports. From the newspaper submissions, backed by extensive research to document details and explain allusions, western writer Chuck Parsons has fashioned an annotated compendium of primary materials that give insight into not only the life and actions of the famous Texas Rangers but also the popular culture of post?Civil War Texas. Robinson rode with McNelly as the Rangers subdued the clashes between the Suttons and the Taylors in DeWitt County. He served on the Rio Grande frontier in actions against Juan Cortina, including the famous battle on Palo Alto Prairie. He was with a party of Rangers who invaded Mexico to recover cattle stolen from Texas ranchers. Pidge?s lively, literate, and often humorous letters give first-person accounts of these and other actions that provide a unique picture of Ranger service in the field. This Texas A & M University Press edition, incorporating newly discovered materials, also features rare period photographs, illustrations, and other helpful maps and images.--Amazon.com.